2021
DOI: 10.1093/hmg/ddab100
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of SERCA ameliorates dystrophic phenotypes in dystrophin-deficient mdx mice

Abstract: Duchenne muscular dystrophy (DMD) is an X-linked genetic disorder characterized by progressive muscular weakness due to the loss of dystrophin. Extracellular Ca2+ flows into the cytoplasm through membrane tears in dystrophin-deficient myofibers, which leads to muscle contracture and necrosis. Sarco/endoplasmic reticulum Ca2+-ATPase (SERCA) takes up cytosolic Ca2+ into the sarcoplasmic reticulum (SR), but its activity is decreased in dystrophic muscle. Here, we show that an allosteric SERCA activator, CDN1163, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…50% in de novo lipogenesis contributes to the dysfunction of sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA) activity, whereas the recovery of this pathway through the overexpression of lipogenic factors mitigates SERCA function by affecting the composition of the sarcoplasmic reticulum membrane 66 . Of note, pharmacological activation of SERCA was recently demonstrated to provide a promising therapeutic strategy for DMD 67 . Moreover, apart from lipogenic genes, we observed decreased expression of the gene encoding lipid droplet coat protein perilipin 2 ( Plin2 ) in dystrophic livers, similarly to the findings reported by Murphy et al 32 on protein level, further emphasizing the perturbations in lipid homeostasis displayed by dystrophic animals.…”
Section: Discussionmentioning
confidence: 99%
“…50% in de novo lipogenesis contributes to the dysfunction of sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA) activity, whereas the recovery of this pathway through the overexpression of lipogenic factors mitigates SERCA function by affecting the composition of the sarcoplasmic reticulum membrane 66 . Of note, pharmacological activation of SERCA was recently demonstrated to provide a promising therapeutic strategy for DMD 67 . Moreover, apart from lipogenic genes, we observed decreased expression of the gene encoding lipid droplet coat protein perilipin 2 ( Plin2 ) in dystrophic livers, similarly to the findings reported by Murphy et al 32 on protein level, further emphasizing the perturbations in lipid homeostasis displayed by dystrophic animals.…”
Section: Discussionmentioning
confidence: 99%
“…CDN1163 increased ER Ca 2+ content, rescued ERS-induced neuronal death in vitro , and showed significant efficacy in a 6-hydroxydopamine-induced Parkinson’s disease rat model ( Dahl, 2017 ). The dystrophic phenotype of dystrophin-null transgenic mice was ameliorated by CDN1163, which effectively prevented exercise-induced muscle damage and restored mitochondrial function ( Nogami et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that the absence of dystrophin in the dystrophinopathies, like DMD, triggers skeletal muscle fibre necrosis due to pathological [Ca 2+ ] in regulation (Allen et al ., 2016). Several studies have shown that the skeletal muscle pathology in the dystrophin deficient mdx mouse can be ameliorated by overexpressing or pharmacologically activating the SR Ca 2+ pump, SERCA1 (Goonasekera et al ., 2011; Mázala et al ., 2015; Nogami et al ., 2021). Previously, our group has shown that one consequence of the Actn3KO is a marked increase of SERCA1 protein in fast-twitch skeletal muscle (Head et al ., 2015; Garton et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We found convincing correlative evidence that the age related protective effect conferred by the absence of α-actinin-3 is due to the reduction in the number and complexity of pathologically branched dystrophic fibres. Additionally, we propose that the mechanism by which the polymorphism R577X induces this protective effect in the dystrophinopathies is due to a switch in the fast-twitch fibres to a more glycolytic metabolism and an increase in the SERCA1 pumps, both of which are known to be protective in the dystrophinopathies (Goonasekera et al ., 2011; Head et al ., 2015; Mázala et al ., 2015; Garton et al ., 2018; Kiriaev et al ., 2021a; Nogami et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%